ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN PROSEDUR NEWMAN PADA KELAS XI MIPA 1 SMAN 5 PADANG - Devin Mernovina Sari (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
The purpose of this study was to determine the types and causes of errors made by students in solving story problems of geometric rows and series material based on Newman's procedure. This research uses qualitative research with descriptive type, the research subject consists of 3 students from 40 students of class XI MIPA 1 SMAN 5 Padang, with the criteria of 1 student each from high, medium, and low groups. Data collection was done by test and interview. Error analysis using Newman's criteria. The results showed that the percentage of students' errors in solving story problems related to the material of geometric rows and series based on Newman's procedure were: (a) the percentage of comprehension errors made by students amounted to 34.63%, (b) the percentage of transformation errors amounted to 16.28%, (c) the percentage of process skill errors amounted to 14.91%, and (d) the percentage of errors in writing the final answer (Encoding Error) amounted to 34.18%. The causes of student errors include, rushing to understand the problem, not writing the known and questionable things in the problem, not focusing on working on the problem, not being careful in carrying out the calculation process, not being accustomed to writing conclusions, and rushing the solution process. Keywords: Error Analysis, Story Problem, Newman Procedure